Deep learning methods for scene text detection - Liu, Zichuan (Nanyang Technological University, 2020)
Optical Character Recognition (OCR) is a common method to convert typed, hand-written or printed text from documents and scene photos into digital format, which can be edited, searched, stored and displayed. It acts as a uniform information entry for text related higher-level applications, such as cognitive computing, machine translation text-to-speech, and data mining.